An Epidemiological Study on Pattern of Smoking, Alcohol and Other Drugs Consumption among Femal Tea Pluckers in Nuwara-Eliya District, Sri Lanka (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Introduction : Smoking and alcohol consumption among the estate population are considered to be high. However there is little documented evidence on the prevalence of smoking and alcohol consumption among female estate workers in Sri Lanka. The aim of this study was to find out the prevalence of smoking, alcohol and other dugs consumption among female estate workers and to find out factors associated with these habits. Methodology : A community based cross sectional study was carried out with a sample of 928 females on a presumptive prevalence of 10% of alcohol users, using simple random sampling technique. Data was collected by trained field public health midwives using an interviewer administered questionnaire. Statistical analysis of data was carried out using SPSS version 11. Results : The response rate was 97.8%. Prevalence of smoking, alcohol and other drugs were 7.27%, 34.7% and 0% respectively. Among smokers, most smoked cigar (55%), followed by Beedi (39%) and cigarette (6%). None indulged in dangerous drugs like Heroin and cannabis. Most consumed alcoholic beverage was toddy (64%) followed by arrack (31%). Seventy four percent of women stated that they consume alcohol because they were influenced by their husbands. A significant positive association was observed between smoking and (a)illiteracy (p